FSI Analysis of TLP Tether System for Floating Wind Turbine - Zheng-Shou Chen; Wu-Joan Kim; Jae-Hoon Yoo (Han-guk haeyang gonghak hoeji (Online), 2010)
ANSYS multi-physics software was applied to solve the coupled dynamic problem related to a full-scale TLP foundation for floating wind turbines. In this coupled dynamics simulation, the forced oscillation imposed on the tethers’ top resulting from the sway of the wind turbine platform and the self-excited vortex-induced vibration (VIV) along the tether span have been taken into account. The stability of this tensioned tether system has been validated in the form of separate static and dynamic analyses. The dynamic characteristics of the tensioned tether linked to the floating wind turbine were analyzed by the resultant modal form and its corresponding vortex shedding pattern. The calculated result shows that even a slight forced oscillation imposed on the tethers’ top leads to the VIV amplification and enhances the risk of instability in the case of low pretension. It is also found that the “synchronization” would be aggravated when the top tension decreases and the “2P” vortex shedding mode takes place. The increased top tension imposed on the tethers contributes to the stability of the tensioned legs by diminishing the oscillation amplitude markedly. KCI Citation Count: 1